Rehabilitation of military men with insufficiency of the feed, received wounds during carrying out of counterterrorist operation in Dagestan in 1999 - A. M. Amirov (Юг России: экология, развитие)
The article deals with problems of patho-genetic mechanism of insufficiency of wounded people’s feeding, practicability of the use of the balanced mixtures in their complex treatment. The positive dynamics of majority of factors of wounded people’s psycho-physiological state when using the "Nutridrink" preparation in the course of their clinical rehabilitation has been revealed. In the dynamics the improvement of all studied factors of wounded people’s life quality has been brought into the light during undertaking the nutritional support.